Think Talk Write Strategy toward Students’ Writing Ability - Rizka Indahyanti (Ethical Lingua: Journal of Language Teaching and Literature, 2017)
The objective of this research was to find out whether or not the implementation of Think Talk Write (TTW) strategy improves students’ writing ability. The researcher applied quasi-experimental method. The population of this research is the second semester students of English Language Education. There were two classes and it consists of 60 students. The researcher used cluster random sampling technique and divided the class into two groups, one group as experimental group and another as control group. Therefore, each group consisted of 30 students. Based on the students’ result obtained and stated in findings, the researcher used t-test in inferential statistic through SPSS to test the hypothesis. It showed that the probability value is lower than alpha (α) (0.000 < 0.05). It means that H1 was accepted and H0 was rejected. Therefore, it can be concluded that the implementation of Think Talk Write (TTW) strategy improves students’ writing achievement.